2023
DOI: 10.1017/cft.2023.4
|View full text |Cite
|
Sign up to set email alerts
|

Blue justice: A review of emerging scholarship and resistance movements

Abstract: Coastal communities, Indigenous peoples, and small-scale fishers are intimately connected with the ocean. Yet, these historically and structurally marginalized groups often bear a disproportionate distribution of coastal and marine harms, and are culturally and politically excluded from marine decision-making. In response, calls for blue justice are emerging. Here, we review key perspectives, new developments, and gaps in the emerging blue justice scholarship. We also synthesize existing case studies of blue i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“…The full potential of such alternative legalities goes unrecognized by ocean governance regimes despite their promising role to inform marine governance policies. While research has shown the benefits and challenges of local communities' activism to advance ocean justice by asserting customary rights as a resistance strategy (Bennett et al, 2023;Blythe et al, 2023), the studies of Arieli (2012) and Song (2021) suggest that cross-border synergies and their involvement in border-crossing management contribute to regional prosperity and stability, diffusing "political tension and [catalyzing] a cooperative framework towards the resolution of maritime disputes" (Song, 2021, p. 10). As this author points out, while state-state agreements can take several years to be implemented, bottom-up local agreements among stakeholders usually include short-term and common activities in the line of communities' shared needs, which supersede sovereignty issues.…”
Section: Discussion: Maritime Borders and Indigenous Sea Mobilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The full potential of such alternative legalities goes unrecognized by ocean governance regimes despite their promising role to inform marine governance policies. While research has shown the benefits and challenges of local communities' activism to advance ocean justice by asserting customary rights as a resistance strategy (Bennett et al, 2023;Blythe et al, 2023), the studies of Arieli (2012) and Song (2021) suggest that cross-border synergies and their involvement in border-crossing management contribute to regional prosperity and stability, diffusing "political tension and [catalyzing] a cooperative framework towards the resolution of maritime disputes" (Song, 2021, p. 10). As this author points out, while state-state agreements can take several years to be implemented, bottom-up local agreements among stakeholders usually include short-term and common activities in the line of communities' shared needs, which supersede sovereignty issues.…”
Section: Discussion: Maritime Borders and Indigenous Sea Mobilitiesmentioning
confidence: 99%
“…More recently, by highlighting the human dimension of the oceans, researchers and policy-makers have raised awareness of the inequalities, dispossession, marginalization, and exclusion of coastal people, including women, fish workers, and indigenous peoples (Allison et al, 2020). By doing so, ocean justice scholarship now includes indigenous and grassroots resistance initiatives demanding justice by contesting exclusion, voicing equal access and opportunities, and proposing alternatives to Western, economy-driven governance processes (Blythe et al, 2023). Although studies in this area have lately been gathered under the banner of 'blue justice' scholarship, I use its broadest definition, in which ocean justice includes, but also goes beyond, the blue-economy and marine resources management counter-narrative, thus including spatial and mobility justice issues.…”
Section: Theoretical Vantagepointsmentioning
confidence: 99%
“…Failing to address any of these dimensions may result in reproducing historical injustices and simply "kicks the tipping point down the road". Resistance movements such as Blue Justice, a grassroots initiative to safeguard a secure and viable space for small-scale fisheries in the blue economy (Blythe et al, 2023), are examples of what is needed to ensure that the fundamental structures of unsustainability are dismantled.…”
Section: Mainstream Equity and Justice Into The Governance Of Ptpsmentioning
confidence: 99%
“…First, it matters for the fairness and equity of conservation measures (Bennett, 2022). Depending on the level of protection of an MPA, fishers are often the most exposed to changes in access following its creation (Beger et al, 2004; Blythe et al, 2023; Gill et al, 2023; Horta e Costa et al, 2016; Maypa et al, 2012). Second, their participation in assessing the conservation and potential fisheries outcomes is key to its success as it can increase their general participation to management processes and empower them (Twichell et al, 2018; Uychiaoco et al, 2005).…”
Section: Introductionmentioning
confidence: 99%